Green Synthesis of Copper Nanoparticles: Evaluation of Catalytic and Antibacterial Activity - Reddeppa, M.; Krishna Reddy, R. Chenna; Raj, Y. Paul; Rani, T. Shobha (Asian Journal of Chemistry, 2019)
The objective of present study is to synthesize copper nanoparticles from Vitex negundo Linn., root bark extract as reducing and stabilizing agents. The synthesized nanoparticles were characterized by using UV-visible spectrophotometer, X-ray diffraction, FTIR, SEM and EDX. The results were shown that copper nanoparticles exhibited UV-visible absorption peak at around 550 nm. The XRD study confirmed that nanoparticles are crystalline in nature. In addition to these, FTIR was also used to analyze the various functional groups stabilized and protected the copper nanoparticles. The SEM results revealed that the copper nanoparticles are spherical, cubic and hexagonal in shape and having the particle size ranging from 40 to 60 nm. Catalytic activity of copper nanoparticles were studied in the Huisgen [3+2] cycloaddition of azides and alkynes to obtain 1,4-disubstituted 1,2,3-triazole at room temperature. Antibacterial profile revealed that the biopotent copper nanoparticles exhibited moderate to good activity against bacterial strains.